Exchange rate volatility and news effects: an application with the Turkish daily data - Demiröz, Dündar Murat (My University, 2000)
The main aim of this thesis is to estimate the daily volatility of four foreign currencies, namely the American Dollar, the German Mark, the French Franc and the English Sterling. By using various time varying volatility models daily foreign exchange volatility has been estimated. Furthermore, the impacts of political and macroeconomic news effects have also been analysed. In daily level, foreign exchange volatility may be influenced by several public announcements, including macroeconomic announcements, (money supply changes, interest rates, Central Bank's open market operations and etc.) and political facts (elections, and other shifts in the political environment.). To investigate the possible relationship between these news effects and foreign exchange volatility, a three step method has been implemented. In the first step, the estimation of volatility parameters has been conducted. In the second step the volatility forecasting experiment has been implemented. In the final step the forecasted volatility is used asses the impacts of news effects on the foreign exchange volatility. For the estimation, the daily data between 01.06.1994 and 31.08.1998 are processed, where the estimated parameters are used to forecast the future volatility. To test the forecasting efficiency of the models, the actual data between 01.09.1998 and 31.08.1999 are used. Depending on various statistical criteria, the most convenient model for forecasting is chosen. Finally, the effects of macroeconomic announcements and other public information components on the forecasted volatility of daily foreign exchange rates are measured. The results of the paper illustrates that foreign exchange volatility is influenced by negative foreign exchange returns more than by positive returns. It is also found that any unexpected change in foreign exchange returns rates do not affect the volatility for the long term. This result differs from previous studies, where a symmetric behaviour and long term persistence in foreign exchange volatility is found. The reason of this finding can be explained by the high chronic inflation existing in Turkish economy and high uncertainty in socio-political environment. It is observed that the interest rates and the Central Bank's interventions are the most effective factors in explaining the volatility of foreign exchange rates. The closure effects aand the financial crises are found to be influential on forecasted volatility.

Bu tezin ama amacı, Amerikan Doları (USD), Alman Markı (DEM), Fransız Drangı (FRF) ve İngiliz Sterlin' inden oluşan dört döviz kurunun, sekiz otoregresif heteroskedastisite modelini uygulayarak, günlük volatilitesini tahmin etmek ve makro iktisadi haber etkilerinin bu volatiliteye olan tesirlerini ölçmektir. Günlük seviyede, döviz kuru volatilitesi bazı kamuya açık duyurulardan etkilenebilir, ki bu duyurular makro iktisadi duyuruları, (örneğin, para arzı değişiklikleri, faiz hadleri, Merkez Bankası'nın açık piyasa işlemleri gibi), ve siyasi olguları, (örneğin seçimler ve siyasi ortamda meydana gelen benzeri değişiklikler), içermektedir. Döviz kuru volatilitesi ve bu haber etkileri arasındaki ilişkiyi incelemek için üç aşamalı bir süreç izlenmiştir. Birinci aşama volatilite parametrelerinin tahmin edilmesi, ikinci aşama ileriye yönelik öngörülerin oluşturulması ve üçüncü aşama da bu öngörülen volatilite ile haber etkilerinin regresyona tabi tutulmasıdır. Tahmin için, 01.06.1994 ve 31.08.1998 dönemine ait günlük veriler kullanılmıştır. Daha sonra, tahmin edilen parametrelerden gelecekteki volatilitenin öngörülmesi aşamasında yararlanılmıştır. Her modelin öngörü etkinliğini ölçmek amacıyla, 01.09.1998 ve 31.08.1999 dönemine ait veriler kullanılmıştır. İkinci aşamada, çeşitli istatistik kriterlere dayanarak ileriye yönelik örneklem dışı öngörüler için en uygun model tespit edilmiştir. Üçüncü aşamada, makro iktisadi duyuruların ve diğer kamuya açık bilgi bileşenlerinin döviz kuru volatilitesinin örneklem içi öngörüleri üzerindeki etkileri ölçülmüştür. Çalışmanın sonuçlarına göre döviz kuru volatilitesi asimetrik bir davranış göstermektedir ve bilgi şoklarının bu volatilite üzerindeki etkileri ancak kısa dönemli bir kalıcılık arz etmektedir. Bu sonuç, Baillie ve McMahon (1989) ve Bollerslev, Chou ve Kroner'in (1992)daha önce çalışmalarında bildirdikleri sonuçlardan farklılık göstermektedir. Bu ise Türkiye'de uzun yıllardır süregelen yüksek kronik enflasyonun anormal karakteri ile açıklanabilir. Çalışmanın üçüncü aşamasında elde edilen bulgulara göre, faiz hadleri ve Merkez Bankası'nın piyasaya müdahaleleri döviz kuru volatilitesini açıklayan faktörler arasında en etkili olanlarıdır. Bulgular, döviz kurlarının tahmin edilmiş volatilitesinin asimetrik karakteri ile de tutarlılık göstermektedir; şöyle ki, volatilite üzerinde merkez bankasının döviz kurlarını düşüren satışları, yükselten alışlarından daha etkili olduğu tahmin edilmiştir. Bütün bunları yanında, piyasa kapanışları ve mâli krizlerin de günlük volatilite üzerinde etkili olduğu saptanmıştır.
Keywords: Döviz Kurları-Türkiye; Döviz-Türkiye